Effect of Scaffolding and Peer Review on Learning in a PAD Class - Lihong Ding; Jirarat Sitthiworachart; John Morris (World Journal of English Language, 2023)
We investigated the effectiveness of peer review in the PAD class teaching mode in a university English course in northwest China using both qualitative and quantitative methods; we collected data through teaching platform observation, text analysis, and questionnaires. 378 useable responses were received from non-English major undergraduates.Peer review assignments in the PAD class improved the autonomy, collaboration and critical consciousness of university students in learning English. The active participation, help, question raising and problem solving of peers allowed students to improve their English. In the correlation analysis, the three dimensions：peer feedback analysis; analysis of online speech; discussion, and writing analysis of questionnaire survey of peer review showed significant correlation in a peer review survey (p<0.01). Among them, the attitude and evaluation ability of peer review were related to "subjective initiative, critical thinking, learning ability and evaluation ability to promote learners' English application ability", and the organization way of peer evaluation was related to "open mind and systematic ability". There were strong correlations between the evaluation criteria of peer assessment and "systematic ability and cognitive maturity" (0.6<r<0.8). The other dimensions were very strongly correlated (r>0.8).Peer review in the PAD class mode was effective; most learners showed a positive attitude towards this method; adopting it can not only avoid increasing teacher workload, but also gave multidimensional feedback to the teachers about student learning situations. It can also guide the second language learners to improve their learning methods.
Keywords: Second Language Learning and Teaching; Educational Technology and Assessment; Student Assessment and Feedback